The indigenous issue in a multidisciplinary context PIBID action in school./A questão indígena em contexto multidisciplinar: ação do PIBID na escola. - Naésia Daiane dos Santos Silva; Flaviana dos Santos Silva; Natália Bandeira de Almeida; Tereza Cristina Cavalcante de Albuquerque (Universidade Estadual de Alagoas, 2020)
This article discusses the didactic project "Indigenous Roots of Alagoas" which, from the perspective of a training based on Law 11.645 / 08, which makes the teaching of Afro-Brazilian and Indigenous History and Culture incorporated into the school curriculum, provided the development of multidisciplinary interventions in the elementary school class. The project was carried out through PIBID (Institutional Program for Teaching Initiation Scholarships) by students of the Pedagogy course at the Federal University of Alagoas - Arapiraca Campus, in one of the Arapiraca municipal schools in the state of Alagoas with a class of 2 1st year of elementary school.